Safety Management for Unmanned Aviation - Peter STASTNY (National Institute for Aerospace Research “Elie Carafoli” - INCAS, 2021)
In Air Traffic Management (ATM), Safety Management Systems (SMS) provide the principal vehicle for implementing safety policies, practices and procedures in accordance with internationally agreed Standards. In a constantly changing operating environment, it is essential to maintain SMS effectiveness to maintain and enhance levels of ATM safety. Research at the University Politehnica of Bucharest (UPB) has analysed the major, fast-rising threats to ATM safety emerging in the field of unmanned aviation. After considering the operating environment in terms of control arrangements and unmanned vehicle types, the relationship between ATM and Unmanned Traffic Management (UTM) is examined. It is concluded that the SMS supporting ATM requires enhancement to address the risks arising from the emergence of unmanned aviation and relevant enhancement measures are therefore proposed. Further, research shows that detailed safety management arrangements to support UTM are not yet defined. Indicative SMS requirements for UTM are therefore derived and presented.